Stress & Success: A study on Workplace Stressors and Performance among Female Bank Employee in Nepal - Yadav, Indra (International Research Journal of MMC, 2025)
Workplace stress is a significant issue, particularly for female employees in high-pressure environments like banking. The background of this research stems from the growing concern over how stressors such as workload, job security, shift scheduling, and role ambiguity affect the performance and well-being of female employees in the banking sector.The main goal of this study is to find the main sources of stress at work and look at how they affect the work performance of Nepalese female bank workers. A structured questionnaire was used to get information from 250 female employees as part of a quantitative study design. We used both correlation and regression analyses to find the link between stressors and job performance. The findings reveal that all identified stressors—workload, job insecurity, shift scheduling, and role ambiguity—have a significant negative effect on employee performance. Shift scheduling explained 23.5% of the variation in performance, while role ambiguity accounted for 16.7%. The results highlight that higher levels of stress are associated with lower job performance, leading to the rejection of null hypotheses related to the impact of shift scheduling and role ambiguity. The originality of this study lies in its focus on the specific challenges faced by female bank employees in Nepal, providing valuable insights into how workplace stressors impact job performance in this context. The results make it clear that effective stress management methods are needed to boost the health and productivity of workers.